Financial Relations Between Central Government and Regional Government in Regional Autonomy - JENERIO, Rio; WATI, Wilna; JAMILAH, Fitria Lailan; TUAHNU, Bernandus; KRISTHY, Mutia Evi (Journal of Political And Legal Sovereignty, 2023)
Purpose: Law Number 23 of 2014 concerning Regional Government shows a division of authority between the Central Government, Provincial Government, and City Regency Government. Mapping or classification of central and local government affairs is regulated in Article 9 to Article 26.Methodology:The method used in research for writing this paper is to use the type of research "Normative," namely by using secondary data. Normative Law Research is research conducted on laws and regulations related to the legislation in this paper. In addition, by conducting a literature review of related literature.Findings: With regional autonomy, the government in the region in running the government requires costs to take care of its household for the region to get money; a source of regional income is needed.Implication:The Financial Relationship between the Central Government and Regional Government has been established by Law Number 1 of 2022 concerning Financial Relations between Central and Regional Governments, which repealed Law Number 28 of 2009 concerning Regional Taxes and Regional Levies and Law Number 33 of 2004 concerning Financial Balance between the Central Government and Regional Governments.